Dynamics of blaKPC-2 Dissemination from Non-CG258 Klebsiella pneumoniae to Other Enterobacterales via IncN Plasmids in an Area of High Endemicity (2020)
ABSTRACT: Carbapenem-resistant Enterobacterales (CRE) pose a significant threat to global public health. The most important mechanism for carbapenem resistance is the production of carbapenemases. Klebsiella pneumoniae carbapenemase (KPC) represents one of the main carbapenemases worldwide. Complex mechanisms of blaKPC dissemination have been reported in Colombia, a country with a high endemicity of carbapenem resistance. Here, we characterized the dynamics of dissemination of blaKPC gene among CRE infecting and colonizing patients in three hospitals localized in a highly endemic area of Colombia (2013 and 2015). We identified the genomic characteristics of KPC-producing Enterobacterales recovered from patients infected/ colonized and reconstructed the dynamics of dissemination of blaKPC-2 using both short and long read sequencing. We found that spread of blaKPC-2 among Enterobacterales in the participating hospitals was due to intra- and interspecies horizontal gene transfer (HGT) mediated by promiscuous plasmids associated with transposable elements that was originated from a multispecies outbreak of KPC-producing Enterobacterales in a neonatal intensive care unit. The plasmids were detected in isolates recovered in other units within the same hospital and nearby hospitals. The gene “epidemic” was driven by IncN-pST15-type plasmids carrying a novel Tn4401b structure and non-Tn4401 elements (NTEKPC) in Klebsiella spp., Escherichia coli, Enterobacter spp., and Citrobacter spp. Of note, mcr-9 was found to coexist with blaKPC-2 in species of the Enterobacter cloacae complex. Our findings suggest that the main mechanism for dissemination of blaKPC-2 is HGT mediated by highly transferable plasmids among species of Enterobacterales in infected/colonized patients, presenting a major challenge for public health interventions in developing countries such as Colombia.